Part D Formulary and Benefit Design as a Risk-Steering Mechanism - Goldman, Dana P; Joyce, Geoffrey F; Vogt, William B (American Economic Review, 2011)
Medicare Part D relies upon drug plan competition. Plans have enormous scope to design benefits and to set premiums, but they may not charge differential premiums based on risk. We use the formulary and benefit design of all Medicare prescription drug plans and pharmacy claims data to construct a simulation model of out-of-pocket drug spending. We use this simulation model to examine individual incentives in Medicare Part D for adverse selection. We find that high drug users have much stronger incentives to enroll in generous plans than do low users, thus there is significant scope for adverse selection.